Generation of cesium lead halide perovskite nanocrystals via a serially-integrated microreactor system: Sequential anion exchange reaction - Kang, Sung Min; Park, Bumjun; Raju, Ganji Seeta Rama; Baek, Seungmin; Hussain, Sk Khaja; Kwak, Cheol Hwan; Han, Young Kyu; Yu, Jae Su; Kim, Sang Wook; Huh, Yun Suk (Chemical Engineering Journal, 2020)
Inorganic perovskite nanocrystals (NCs) of cesium lead mixed halides (CsPb(X/Y)3, X = Br, Y = Cl and I) are promising optical materials for developing the high-performance photonic devices. Traditionally, anion-exchange reaction in perovskite halide NCs provides a simple substitutional way to tune the composition and emitting color with good luminescence properties in the human eye detectable visible spectral regions. However, prior synthetic procedures of perovskite NCs have employed conventional flask-based reactions which limit the fine control of perovskite NCs because of extremely fast anion-exchange kinetics. To overcome such problems, we demonstrate a droplet-based microfluidic system with simple, fast, and high-throughput parametric screening for the synthesis of perovskite NCs. By using the customized microfluidic operational system consisting of serially integrated two microfluidic reactors and heating block, we have successfully synthesized CsPbX3 perovskite NCs. In addition, we can finely control the anion-exchange reaction which can generate the formation of CsPb(X/Y)3 perovskite NCs with a wide range of visible spectrum (410–630 nm). Ultimately, we have established their potential applications in the development of solid-state lighting-based flexible display systems.
Keywords: Anion exchange; Droplet-based microfluidics; Flexible display systems; Luminescence properties; Micro-fluidic reactors; Solid state lighting; Synthetic procedures; Visible spectral regions; Anion exchange; Metal halides; Microfluidics; Optoelectronics; Perovskites; Photoluminescence